Implementasi Virtual Reality pada Game Edukasi Protokol Kesehatan - Gerry Jeven Timoti; Yohannes Yohannes; Yoannita Yoannita (Jurnal Teknik Informatika dan Sistem Informasi, 2022)
In the year of 2020 until now has been a tough year for almost all industries and the general public due to the coronavirus pandemic. However, the increase in cases per day illustrates that the community has not complied with health protocols optimally. The impact of the pandemic has increased gamers in Asia by more than 75%. With a positive impact on society, the role of games can be used as a medium for education. Virtual Reality will be implemented in the health protocol educational game to see the good role of virtual reality in educational game interactions. The implementation of Virtual Reality in the health protocol educational game is carried out using the GDLC (Game Development Life Cycle) approach with stages starting from initiation, pre-production, production, testing, and release. The results of the recapitulation of the questionnaire on the acceptance and satisfaction of the health protocol educational game application showed the results of 44,9.% strongly agree, 44,9% agree, 9,15% are neutral and 1% are not agree that the application has functioned well and can be selected as one of the learning media especially about health protocol to reduce the growth rate of people infected with the coronavirus.